Early selection of novel triploid hybrids of shrub willow with improved biomass yield relative to diploids - Serapiglia, Michelle J (BioMed Central, 2014)
BACKGROUND: Genetic improvement of shrub willow (Salix), a perennial energy crop common to temperate climates, has led to the development of new cultivars with improved biomass yield, pest and disease resistance, and biomass composition suitable for bioenergy applications. These improvements have largely been associated with species hybridization, yet little is known about the genetic mechanisms responsible for improved yield and performance of certain willow species hybrids. RESULTS: The top performing genotypes in this study, representing advanced pedigrees compared with those in previous studies, were mostly triploid in nature and outperformed current commercial cultivars. Of the genotypes studied, the diploids had the lowest mean yield of 8.29 oven dry Mg ha(−1) yr(−1), while triploids yielded 12.65 Mg ha(−1) yr(−1), with the top five producing over 16 Mg ha(−1) yr(−1). Triploids had high stem area and height across all three years of growth in addition to greatest specific gravity. The lowest specific gravity was observed among the tetraploid genotypes. Height was the early trait most correlated with and the best predictor of third-year yield. CONCLUSIONS: These results establish a paradigm for future breeding and improvement of Salix bioenergy crops based on the development of triploid species hybrids. Stem height and total stem area are effective traits for early prediction of relative yield performance.